Brood parasites lay eggs matching the appearance of host clutches - Honza, Marcel; Šulc, Michal; Jelínek, Václav; Požgayová, Milica; Procházka, Petr (Proceedings. Biological sciences, 2014)
Interspecific brood parasitism represents a prime example of the coevolutionary arms race where each party has evolved strategies in response to the other. Here, we investigated whether common cuckoos (Cuculus canorus) actively select nests within a host population to match the egg appearance of a particular host clutch. To achieve this goal, we quantified the degree of egg matching using the avian vision modelling approach. Randomization tests revealed that cuckoo eggs in naturally parasitized nests showed lower chromatic contrast to host eggs than those assigned randomly to other nests with egg-laying date similar to naturally parasitized clutches. Moreover, egg matching in terms of chromaticity was better in naturally parasitized nests than it would be in the nests of the nearest active non-parasitized neighbour. However, there was no indication of matching in achromatic spectral characteristics whatsoever. Thus, our results clearly indicate that cuckoos select certain host nests to increase matching of their own eggs with host clutches, but only in chromatic characteristics. Our results suggest that the ability of cuckoos to actively choose host nests based on the eggshell appearance imposes a strong selection pressure on host egg recognition.
Keywords: Ovum; fyziologická adaptace; vaječná skořápka; egg coloration; Color; Birds; barva; rozpoznávání (psychologie); egg mimicry; ovum; Nesting Behavior; great reed warbler; zvířata; cuckoo; Egg Shell; Recognition, Psychology; brood parasitism; ptáci; hnízdění; Adaptation, Physiological; Animals